Description of final stadium larva of Dysphaea gloriosa Fraser, 1938, (Odonata: Euphaeidae) with notes on its habitat and biology - Nguyen, Minh Ty; Ignatius, Kaewpawika Jitthamma; Sunprasit, Somneuk; Phan, Quoc Toan; Keetapithchayakul, Tosaphol Saetung (Zootaxa, 2024)
The final instar larva of the genus Dysphaea Selys, 1853 is described and figured for the first time based on specimens of D. gloriosa Fraser, 1938 from Khao Yai National Park, Thailand. The larvae of D. gloriosa are very rarely encountered. The larvae are characterized by the relatively larger head, the swollen heavily spined genae extending well beyond the eyes, the swollen postocular lobes bearing a disordered row of dense strong marginal spines, the outer armature of the mandibles and the unusual labrum. Notes on the habitat and biology of the larvae are also provided.